2018
DOI: 10.4236/pst.2018.61001
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Pattern for Skin Diseases in Dermatology OPD at Borumeda Hospital, North East, Ethiopia

Abstract: Introduction: Skin diseases are the major contributors of disease burden in society. Dermatological therapy ultimate goal is achieved by administering the safest and least number of drugs. The problem gets compounded with the inappropriate and irrational use of medicines. Therefore, periodic prescription audit in the form of prescribing patterns is away to improve irrational prescription. The objective of this study to assess the prescription patterns of dermatological agents in Borumeda hospital. Method: Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 3 publications
4
4
2
Order By: Relevance
“…Among the Antifungal drugs, Ketoconazole (25.2%) was most commonly prescribed drug followed by Fluconazole (14%) and Clotrimazole (14%). Our results were similar to studies done by Saleem et al (2012); Tegegne and Bialfew (2018).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Among the Antifungal drugs, Ketoconazole (25.2%) was most commonly prescribed drug followed by Fluconazole (14%) and Clotrimazole (14%). Our results were similar to studies done by Saleem et al (2012); Tegegne and Bialfew (2018).…”
Section: Resultssupporting
confidence: 94%
“…Figure 1represents the age wise distribution of patients involved in the study. During the study period, majority of the patients were found in the age group 21-30 years (41.2%) and this result was similar to the studies done by Saleem et al (2012); Tegegne and Bialfew (2018); Sajith and Lokhande (2014). The mean age of the patients Table 1 represents the categorization of drug classes involved in the study.…”
Section: Resultssupporting
confidence: 90%
“…In this study, female number (54.9%) was slightly higher than male number (45.1%) as already been observed in various study of 9 where male to female ratio was 0.88 and 10 where female patients were 50.1%. According to the 11 study conducted at western Nepal 58.2% of female were suffered.…”
Section: Discussionsupporting
confidence: 78%
“…Our results were also similar with the study conducted by 17 where the most common skin diseases pattern seen was primarily tinea 15.25%. Also, the results are different with 10 reported eczema (23.10%), pyoderma (14.29%), fungal infection (14.24%) as the major skin disease. The common fungal infections were dermatophytosis e.g.…”
Section: Discussioncontrasting
confidence: 69%
“…Finally, twelve studies were included in this systematic review and meta-analysis. Of those included studies, eight studies were estimated the prevalence [8,14,[26][27][28][29][30][31] and eight studies were identified associated factor of scabies [14,27,28,[31][32][33][34][35] Fig. 1.…”
Section: Description Of Identified Studiesmentioning
confidence: 99%